Neural Correlates of Narrative Reading Development: A Comparative fMRI Study of Adults and Children Using Time‐Locked Inter‐Subject Correlation Analyses - Li, Jingxiao; Su, Mengmeng; Zhou, Wei (Psychophysiology, 2025)
ABSTRACT The naturalistic paradigm and analytical methods present new approaches that are particularly suitable for research concentrating on narrative reading development. We analyzed fMRI data from 44 adults and 42 children engaged in story reading using time‐locked inter‐subject correlation (ISC), inter‐subject representation similarity analysis (IS‐RSA), and inter‐subject functional correlation (ISFC). The ISC results indicated that for both children and adults, narrative reading recruited not only traditional reading areas but also regions that are sensitive to long‐time‐scale information, such as the medial prefrontal cortex and hippocampus, which increased involvement from children to adults. The results of the IS‐RSA indicated that during narrative reading, children exhibited greater uniqueness in neural patterns, while adults demonstrated greater similarity. The analysis of reading‐level subgroups with the ISC and ISFC reveals differences in narrative reading development that span from children to adults, especially for regions sensitive to long‐time‐scale semantic processing. These results indicate that the maturity and experience play a crucial role in narrative reading development.